2014
DOI: 10.5114/wiitm.2014.46803
|View full text |Cite
|
Sign up to set email alerts
|

Laparoendoscopic single-site surgery adrenalectomy - own experience and matched case-control study with standard laparoscopic adrenalectomy.

Abstract: IntroductionAt our institution, laparoendoscopic single-site surgery (LESS) has been established as a technique for laparoscopic nephrectomy since 2011, and since 2012 in selected cases for adrenalectomy (AE) as well.AimTo compare LESS AE with standard laparoscopic AE (SLAE).Material and methodsBetween 3/2012 and 7/2014, 35 adrenalectomies were performed. In 18 (51.4%), a LESS approach was chosen. Indications were strictly non-complicated cases (body mass index (BMI) < 34 kg/m2, tumour ≤ 7 cm, non-malignant ae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…Some reports describe laparoendoscopic single site (LESS) adrenalectomy as more time consuming compared to the standard laparoscopic procedure [ 17 , 18 ]. The LESS adrenalectomy seems feasible in selected cases, especially small left-sided tumors in thin patients with no history of previous abdominal operations, but may require an additional port in half of the cases [ 19 ]. Robot-assisted adrenalectomy is described to have a shorter hospital stay, less blood loss, and lower occurrence of postoperative complications [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some reports describe laparoendoscopic single site (LESS) adrenalectomy as more time consuming compared to the standard laparoscopic procedure [ 17 , 18 ]. The LESS adrenalectomy seems feasible in selected cases, especially small left-sided tumors in thin patients with no history of previous abdominal operations, but may require an additional port in half of the cases [ 19 ]. Robot-assisted adrenalectomy is described to have a shorter hospital stay, less blood loss, and lower occurrence of postoperative complications [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-two years have passed since the first report on laparoscopic adrenalectomy was published [ 16 ]. Nowadays, minimally invasive surgery in cases of benign adrenal tumors has become a safe method that gives good results [ 6 8 , 17 , 18 ]. However, there is a continuous discussion concerning cases of pheochromocytoma, which can be a challenge to both the surgeon and the anesthetist.…”
Section: Discussionmentioning
confidence: 99%
“…Since the first laparoscopic adrenalectomy by Gagner et al 12 in 1992, in well selected patients, laparoscopic surgery was shown to reduce blood loss, decrease length of stay with quicker commencement of oral intake and return of bowel function. 13 14 15 Single-incision laparoscopic surgery for the adrenal gland, performed either via a retroperitoneoscopic or transabdominal approach, has been gaining popularity, 16 17 18 19 20 with similar outcomes as those of conventional laparoscopic surgery, in addition to improved cosmesis. 16 Ishida et al 20 demonstrated that despite the feasibility of single-incision transumbilical laparoscopic adrenal surgery, there were obvious technical difficulties compared to conventional laparoscopy.…”
Section: Discussionmentioning
confidence: 99%
“… 16 Ishida et al 20 demonstrated that despite the feasibility of single-incision transumbilical laparoscopic adrenal surgery, there were obvious technical difficulties compared to conventional laparoscopy. Hora et al 17 performed single incision laparoscopic adrenalectomies strictly on small tumors with a non-malignant etiology, in their series of 18 cases. In our patient, despite adequate positioning, she had a large floppy liver which was partially obscuring the surgical field.…”
Section: Discussionmentioning
confidence: 99%